StudentsÃ¢â¬â¢ learning creativity by the implementation of contextual-based learning in the subject of natural science - Fifi Faridah; Salahudin Salahudin; Mariamah Mariamah; Muhamad Ajwar (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
One of the competencies needed by students in understanding science concepts is learning creativity. Reality shows that science learning in schools still experience various obstacles. One of which is the low learning creativity of students. The purpose of this study is to develop student learning creativity through contextual-based science learning. This study is an experimental study with a research sample consisting of two classes. The instrument used to measure students' learning creativity was an essay test. The data analysis used was t-test. The results of the analysis obtained a significant value (2-tailed) of 0.000, in the value was less than 0.05, so it is concluded that Ho is rejected or Ha is accepted, which interprets that the application of contextual-based learning can increase student learning creativity.